In contempt - Darden, Christopher A.; Walter, Jess. (New York : HarperAudio, 1996)
Simpson prosecutor Christopher Darden discusses the trial as well as the prejudice he felt from all sides in the frenzy of this "trial of the century."
Abridged.
Read by Christopher Darden.
Keywords: Darden, Christopher A; Trials (Murder) -- California -- Los Angeles; Justice, Administration of -- United States